Coincidence of left isomerism, malposition of cecum, dorsal pancreatic agenesis, and retroaortic left renal vein: A case report - Emekli, Emre; Gündoğdu, Elif; Kebapçı, Mahmut (Journal of Surgery and Medicine, 2019)
Polysplenia / heterotaxy syndrome is a very rare condition that occurs as a result of the maldistribution of the thoracic and abdominal organs. It is examined in two groups with different clinical features and anatomical variations: right and left isomerism. This paper reports the case of a 47-year-old female patient who underwent a non-contrast computed tomography (CT) examination due to right flank pain and suspicion of a renal stone and presented with the findings of left isomerism; i.e., accompanied by intraabdominal variations. On abdominal CT examination, stomach and multiple spleen were localized in the right upper quadrant, and the liver had a midline localization. The interruption of the inferior vena cava with azygos continuation were also detected. The hepatic veins were draining directly into the right atrium. In the literature, a retroaortic left renal vein and dorsal pancreatic agenesis have been individually reported to coexist with left isomerism, but no other case of the coincidence of these three anomalies has been described, which makes the current case report significant. Having knowledge of anatomical variations and clinical status can prevent misdiagnosis, and imaging findings are crucial in the planning of a possible surgical procedure.